2016
DOI: 10.1515/aoas-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low and High Cowshed Temperatures on the Behaviour and Milk Performance of Czech Fleckvieh Cows

Abstract: a group of 98 czech fleckvieh cows (one section) was observed over the period of one year with the aim to determine the variation in their milk performance and behaviour at different cowshed temperatures. behaviour and milk yield were recorded once a week (on the same day) at 10:00. periods of 8 weeks with the highest temperature (hot period -h) and of 8 weeks with the lowest temperature (cold period -l) were then compared. The cows were housed in one section (1/4 of the total capacity) of the free-stall cubic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Still, individual animals showed a marked preference for lying down on a specific side. The choice of lying down on the left side is also confirmed by Vecera et al (2016). Similar observations were recorded by Zejdova et al (2011): i.e., older dairy cows (4 th and higher lactation) prefer the left side more than the younger dairy cows (2 nd and 3 rd lactation) for lying down.…”
Section: Discussionsupporting
confidence: 79%
“…Still, individual animals showed a marked preference for lying down on a specific side. The choice of lying down on the left side is also confirmed by Vecera et al (2016). Similar observations were recorded by Zejdova et al (2011): i.e., older dairy cows (4 th and higher lactation) prefer the left side more than the younger dairy cows (2 nd and 3 rd lactation) for lying down.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, Prelle et al [168] reported that cows that had a consistent milking side preference in the parlour were more fearful under novel situations and dominating over others in the access to resources. Previous studies have also reported that cows who demonstrated a left-side preference in motor functions, like lying [174,175] and passing a novel person [110], produced more milk. However, a high body condition score was found in cows using their right eye during fighting [10].…”
Section: Relationship Between Behavioural Lateralisation and Farm Man...mentioning
confidence: 87%
“…The weak association could be due to general agitation of the cows in noisier environments and the presence of novel sounds in the shelters [ 93 ], which affected the cows but was not detected at the time of our measurements, such as the noise of the shelter machinery and sounding of horns in shelters located near busy highways. Noise therefore clearly impacts on the behaviour of cows and this result suggests that it can adversely affect its welfare, hence this environmental parameter should be considered during designing and construction of cow housing [ 94 ].…”
Section: Discussionmentioning
confidence: 99%